Advanced sliding mode control for solar PV array with fast voltage tracking for MPP algorithm. Issue 10 (23rd August 2020) - Kumar M, Ravi; Satya Narayana, S.; Vulasala, Ganesh
ABSTRACT: This paper presents a photovoltaic (PV) system with a maximum power point tracking (MPPT) method. The main aim of this work is to collect the maximum power generated from a solar photovoltaic generator (PVG). This goal is accomplished by integrating a sliding mode controller (SMC) that drives a voltage source inverter (VSI) connected between the PVG and the load. The system is modelled and tested in MATLAB/SIMULINK. In simulation, the SMC gives a fast and accurate convergence to the MPP that is tracked by incremental conductance (INC) type MPPT algorithm. The consequence of the system is capable of tracking MPPs accurately and rapidly without steady-state oscillation and also its performance is satisfactory. The INC type MPPT algorithm is used to track MPPs because it exhibits a precise control under rapidly changing atmospheric conditions. As the solar energy gives the variable light energy at different times and is not constant, the SMC performance is calculated at variable irradiation points by using one slider gain for the variation of the insolation levels.